Impact of Child Abuse on Sexuality. How to Prevent Short and Long-Term Consequences - Camil Castelo-Branco; David Boada; María Fabiana Reina (Clinical and Experimental Obstetrics & Gynecology)
Objective: To highlight predisposing conditions to Child Sexual Abuse (CSA) and to give tools to healthcare providers to deal with this scourge. Mechanism: A descriptive literature review. Findings in Brief: Nowadays, children and adolescents can be more easily affected by a wide variety of social contingencies that may predispose them to domestic and social violence, such as drug use, early pregnancy, offender behavior, peer violent situations, behavioral disorders, and school dropouts. CSA is not included yet in professional health teams’ training nor considered by authorities who are responsible for implementing preventive measures and public policies, even though presenting considerable magnitude in epidemiologic terms. Pediatricians, general physicians, and other specialists who deal with children and adolescents should incorporate a process of detection for signs and early symptoms of sexual abuse and social actors should put in motion preventive measures. Conclusions: CSA is a concern that should involve the whole society. Actions to reduce its incidence are required in three different targets: social awareness, comprehensive sexuality education, and acting on the predisposing factors.